ANALYSIS OF THE QUALITY OF SIAP PPAK SERVICES FOR THE PROTECTION OF WOMEN AND CHILDREN IN SURABAYA USING E-GOVQUAL - Astuti, Sri Juni Woro; Khusna, Masfufa Zulfa (JPAP: Jurnal Penelitian Administrasi Publik, 2025)
This study aims to analyze the quality of service for the protection of women and children through SIAP PPAK in Surabaya based on the E-GovQual theory (Papadomichelaki & Mentzas, 2012), as well as to identify the supporting factors and constraining factors for its implementation. DP3APPKB Surabaya launched this website-based digital service to facilitate complaints, consultations, and education, but its implementation has not been fully optimized. This study employs a qualitative descriptive approach with six informants comprising managers, internal users, and external users. Data was collected through interviews and analyzed using the Miles, Huberman, and Saldana model. The results of the study indicate that the quality of SIAP PPAK services is quite good in four dimensions of E-GovQual: Efficiency (ease of access), Trust (data security and privacy), Reliability (responsive features), and Citizen Support (community participation and support). The obstacles encountered include limited digital literacy, technical constraints, and a lack of cross-sector coordination outside of working hours. It is concluded that SIAP PPAK requires infrastructure strengthening, increased socialization, and optimization of human resources to maximize services for the protection of women and children.